The Effect of Green Product and Green Advertising on Consumer Purchase Decision LED Lighting - Mustikasari, Anti; Hidayat, Rahmat (International Journal of Engineering and Technology, 2019)
This study examines the company's efforts to increase consumer awareness of the environment through its decision in using Eco friendly products by means observe the effect of green product that the company created as well as the creation of green advertising theme. Method of data collection in this research is by distributing questionnaires for 100 respondents spread in the city of Bandung. The variables studied were Green Product, Green Advertising and Consumer Purchase Decision. Data from the questionnaires were processed using multiple regressions through the application of SPSS version 23. The findings from these studies show if consumers have started to understand the value they will get from using Eco friendly Product while for green advertising theme that emerged has been able to encourage the consumer to make a decision purchase. The empirical results of this study show a difference with previous studies in which Green product in this study had a significant influence on purchasing decisions because of differences in the level of consumer awareness of Eco friendly Product, while for the green-themed ad results are the same that have a significant influence. Simultaneously green products and green advertising can influence buying decisions by 52%. At the end of this study can be considered for the company to creating a green product as consumer needs and how to make green communication could acceptable and capable to increasing customer consumption concern of eco-friendly products.Â Â